Uncertainty propagation analysis in laminated structures with viscoelastic core. (February 2016) - Hernández, W.P.; Castello, D.A.; Ritto, T.G.
Highlights: The sandwich beam is modeled using a classical model of constant shear strain and a first order shear strain theory. Two typical sources of uncertainties on the modal predictions of sandwich beam models was analized. The uncertainty analysis is related to constitutive parameters of the viscoelastic core and a set of geometrical parameters. It is compared the two sandwich models and assess the impact of sources of uncertainties in modal predictions. Abstract: This paper investigates how uncertainties affect the modal parameters of a sandwich structure with a viscoelastic core, which is commonly used in both passive and hybrid control strategies. The viscoelastic sandwich structural component is modelled using (1) the classical model proposed by Mead and Markus and (2) a more complex model that has recently been proposed in the literature. The mechanical behaviour of the viscoelastic core is described by fractional derivative operators. The uncertainties are assumed to come from two sources. The first source of uncertainty is associated with the physical parameters of the constitutive model used to describe the dynamic behaviour of the viscoelastic core, which should be characterised when solving the inverse problem for model calibration. The second source is associated with a set of geometrical parameters and is considered to be linked to both manufacturing processes and assembling–disassembling structural set-ups. A set of examples is performed using the Monte Carlo Simulation analysis, allowing the measurement of the impact of typical sources of uncertainties in modal predictions as well as providing means to make a comparative analysis between two viscoelastic sandwich models. Among other conclusions, it was found that the mean values of the modal parameters do not change much for the different analyses performed, and the thickness of the viscoelastic layer is the most critical variable because it affects both the modal frequency and the damping ratio.